Thermal annealing induced formation of polymeric nanopillars of asymmetric bottlebrush block copolymers. (17th December 2019) - Wang, Qian; Wu, Fan; Luo, Longfei; Shen, Zhihao; Fan, Xing-He
Abstract: Polyhedral polymeric particles are desirable for various applications, but the fabrication is limited due to thermodynamic favorability of sphere formation. Herein, we employed a new strategy to prepare anisotropic nanopillars by thermally annealing bottlebrush block copolymers (BBCPs) with geometric asymmetry. Screw nut-like assembly and hexagonal nanopillars are formed after thermal annealing at 50 °C and 60 °C, respectively, which is rare in self-assembly of block copolymers. The shape transformation of the particles is thermodynamically driven, while the formation of hexagonal nanopillars is mainly attributed to entropic origin (the molecular geometry of the BBCP). This work provides a new strategy to prepare nanomaterials with noval structures. Graphical abstract: Image 1 Highlights: Anisotropic nanopillars are prepared by thermally annealing BBCPs with geometric asymmetry. Screw nut-like assembly and hexagonal nanopillars are formed after thermal annealing at 50  o C and 60  o C respectively in self-assembly of the BBCPs. The shape transformation of the particles is thermodynamically driven, the formation of hexagonal nanopillars is mainly attributed to entropic origin.